UPAYA MENINGKATKAN KETERAMPILAN BERPIDATO DENGAN PAKET BELAJAR MANDIRI PADA KELAS IX SISWA SMPN 2 SEMARANG - Larasati, Larasati (SASINDO, 2013)
The purpose of this study was to describe the speech learning by using self-learning package. Research on learning portrait addressed within the framework of this magnitude isa descriptive study, which was captured from the observation, journals, interviews,documentation, and direct learning. Based on the analysis, media self-learning package forpembelaajaran speech can be said to improve students speaking competence. Increasedcompetence is characterized by positive attitudes and values increased on average by13.65%, from 78.16 to 91.8. Based on these results, it is suggested Indonesian teacher,should be creative in presenting learning, especially speaking skills. Creativity mediaselection and accuracy of the model is very mentukan successful learning. In addition,practitioners of the field of language education and language studies expert, can capitalizeon this research as a basis for improvement of learning and doing similar research withdifferent objects pebelitianKeywords: learning, speech skills, self-contained guide package